Thermoelectric properties of Bi2Te3 disk fabricated from rice kernel-like Bi2Te3 powder - Suriwong T. (Institution of Engineering and Technology, 2015)
© The Institution of Engineering and Technology 2015 Rice kernel (RK)-like bismuth telluride (Bi2Te3) crystals were successfully synthesised by microwave-induced plasma heating of Bi and Te powders. Phase and morphology characterisation revealed the presence of the Bi2Te3 structure in the shape of RKs. The crystal orientation factor (f value) of RK Bi2Te3 powder was larger than that of the RK Bi2Te3 hot-pressed disk. A comparison of the f values of both samples suggested that the RK shape has significant influence in reducing the f value after hot processing. The Seebeck coefficient (S), electrical resistivity (ρ) and thermal conductivity (κ) of the RK Bi2Te3 disk were determined over the temperature ranging from 323 to 623 K. The S value was negative over the whole temperature range, indicating an n-type thermoelectric RK Bi2Te3 disk. The power factor (S2ρ-1) was the highest at about 1.07 × 10-3 W/m K2 at 323 K and decreased with increasing temperature. The maximum dimensionless figure of merit (ZT) of the RK Bi2Te3 disk was 0.26 at about 366 K.